State Management of Labor Migration (As Exemplified by the Sakha Republic [Yakutia]) - Mikhaylova, Anna (International Journal of Economics and Financial Issues, 2016)
The importance of the investigated issue is suggested by the study of the impact of the mass inflow of migrants to the regional labor markets on the life quality of the local community, the development of the infrastructure and the level of social tension in regions. The aim of the paper is to identify features of labor migration in the largest constituent entity of the Russian Federation, the Sakha Republic (Yakutia) and to develop mechanisms for managing labor migration. The leading methods for the research on this issue are social-economic and empirical methods that allow us to reveal the dynamics of labor migration in the region and factors of migration processes. The main results of the research are the following. First, the main migration flows in the region have been identified and characterized. Second, using statistical data dynamics as an example, it has been shown that the main inflow of migrants to the region is observed in the construction industry due to low labor mobility of the local labor market in this industry. Third, strong and weak features of the labor migration in the region have been analyzed based on the sociological research data. Fourth, mechanisms of state management of the labor migration in the region have been developed. The paper may be useful for the researchers in the area of labor migration, labor economists, social and cultural anthropologists, political scientists, as well as for representatives of bodies and structures that are in charge of migration policy and inter-ethnic interaction issues. Keywords: Labor migration; state regulation; international labor migration, regional labor market; development JEL Classifications: J00; J680